Meta‐analysis of risk factors and complications associated with atrial fibrillation after oesophagectomy. Issue 5 (25th March 2019) - Schizas, D.; Kosmopoulos, M.; Giannopoulos, S.; Giannopoulos, S.; Kokkinidis, D. G.; Karampetsou, N.; Papanastasiou, C. A.; Rouvelas, I.; Liakakos, T.
Abstract : Background: Oesophagectomy is associated with high morbidity and mortality rates. New‐onset atrial fibrillation (AF) is a frequent complication following oesophagectomy. Several studies have explored whether new‐onset AF is associated with adverse events after oesophagectomy. Methods: This review was performed according to PRISMA guidelines. Eligible studies were identified through a search of PubMed, Scopus and Cochrane CENTRAL databases up to 25 November 2018. A meta‐analysis was conducted with the use of random‐effects modelling. The I 2 statistic was used to assess for heterogeneity. Results: In total, 53 studies including 9087 patients were eligible for analysis. The overall incidence of postoperative AF was 16·5 per cent. Coronary artery disease and hypertension were associated with AF, whereas diabetes, smoking and chronic obstructive pulmonary disease were not. Patients with AF had a significantly higher risk of overall postoperative adverse events than those without fibrillation (odds ratio (OR) 5·50, 95 per cent c.i. 3·51 to 8·30), including 30‐day mortality (OR 2·49, 1·70 to 3·64), anastomotic leak (OR 2·65, 1·53 to 4·59) and pneumonia (OR 3·42, 2·39 to 4·90). Conclusion: Postoperative AF is frequently observed in patients undergoing oesophagectomy for cancer. It is associated with an increased risk of death and postoperative complications. Abstract : This meta‐analysis assessed risk factors and clinical significance of the development of new‐onset postoperative atrial fibrillation after oesophagectomy. History of coronary artery disease and hypertension increased the risk of new‐onset postoperative atrial fibrillation. Postoperative atrial fibrillation was associated with increased overall mortality, increased risk of an anastomotic leak and increased risk of postoperative pneumonia. Bad news